The relationship between empathy and personality traits in Saudi medical students - Saba Yasien; Fadwa Almuzaini (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Empathy is regarded as a fundamental personal attribute for in-training and in-practice doctors. Several factors may play a significant role to facilitate or prevent the ability of doctors' empathy toward their patients. The objective of the present study is to investigate the relationship of empathy with personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience) among undergraduate medical students. MATERIALS AND METHODS: This study was based on a correlational, cross-sectional design and was conducted from January 2020 to April 2020. The sample consisted of 301 undergraduate medical students studying in different medical colleges situated in Riyadh, Saudi Arabia. Personal information form, the big-five personality inventory, and the interpersonal reactivity index scales were administered. Obtained data were analyzed by applying several methods such as mean, standard deviation, Mann-Whitney U test, Pearson's correlation coefficient, and multivariable linear regression. RESULTS: Regression analysis revealed that personality dimensions accounted for 10-19% of the variance in scores of empathy sub-dimensions of perspective-taking, empathetic concern, fantasy, and personal distress. Agreeableness was found to be associated with empathetic concern and perspective-taking. Openness to experience was found to be significantly related to perspective-taking and fantasy, whereas extraversion was negatively associated with perspective-taking. Neuroticism had an association with personal distress, empathetic concern, and fantasy. Additionally, no gender difference was observed and students with people-oriented specialty preferences showed significantly higher scores on empathy sub-domains than technology-oriented students. CONCLUSION: This study confirmed that personality dimensions play a notable role to predict empathetic behaviors among Saudi undergraduate medical students. This study would help to design individualized strategies by incorporating personality dimensions in the training program to enhance empathetic behavior among medical students.